Scalable Video Coding for Backward-Compatible 360° Video Delivery Over Broadcast Networks - Biatek, Thibaud; Hamidouche, Wassim; Cabarat, Pierre-Loup; Travers, Jean-Francois; Deforges, Olivier (IEEE transactions on broadcasting, 2020)
Recently, the coding and transmission of immersive 360° video has been intensely studied. The technologies provided by standards developing organizations mainly address requirements coming from over-the-top services. The terrestrial broadcast remains in many countries the mainstream medium to deliver high quality contents to a wide audience. To enable seamless introduction of immersive 360° video services over terrestrial broadcast, the deployed technologies shall fulfill requirements such as backward compatibility to legacy receivers and high bandwidth efficiency. While bandwidth efficiency is addressed by existing techniques, none of them enables legacy video services decoding. In this paper, a novel scalable coding scheme is proposed to enable immersive 360° video services introduction over broadcast networks. The experiments show that the proposed scalable coding scheme provides substantial coding gains of 14.99% compared to simulcast coding and introduces a limited coding overhead of 5.15% compared to 360° single-layer coding. A real-time decoding implementation is proposed, highlighting the relevance of the proposed design. Eventually, an end-to-end demonstrator illustrates how the proposed solution could be integrated in a real terrestrial broadcast environment.